2013
DOI: 10.1080/00380768.2013.789395
|View full text |Cite
|
Sign up to set email alerts
|

Potential mineralization and nitrification in volcanic grassland soils in Chile

Abstract: A proportion of the nitrogen (N) applied to grasslands as organic or inorganic fertilizers can be lost to water courses as nitrate and to the atmosphere as nitrous and nitric oxides. Volcanic soils from Chile are not generally prone to leaching, possibly due to net immobilization of nitrate and/or ammonium, and/or due to inhibition of nitrification by either chemical or physical processes. In laboratory studies we found large mineralization potentials in soils from three different Chilean soils after 17 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 43 publications
(41 reference statements)
4
18
2
Order By: Relevance
“…The greater soil N mineralization was measured in the The mineralization values were high and could be related to the high organic matter content of the soil (> 17%), in agreement with Cardenas et al (2013).…”
Section: N Mineralizationsupporting
confidence: 69%
See 2 more Smart Citations
“…The greater soil N mineralization was measured in the The mineralization values were high and could be related to the high organic matter content of the soil (> 17%), in agreement with Cardenas et al (2013).…”
Section: N Mineralizationsupporting
confidence: 69%
“…This deficiency was corrected with the basal nutrients application carried out. Low N available data measured in winter months may be related to immobilization by the microbial biomass and roots (Pérez et al, 1998), as denitrification has been shown to be low in fertilized grassland soils of the same characteristics to that of the present study (Cardenas et al, 2013).…”
Section: Initial Characterizationsupporting
confidence: 52%
See 1 more Smart Citation
“…Cardenas et al. () showed that there is a high N potential retention in the Andisols soil of Southern Chile, which results in periods of high soil N mineralization hiding the effect of N application on productive and nutritive parameters of perennial ryegrass swards.…”
Section: Resultsmentioning
confidence: 99%
“…DNA samples and PCR results failing to meet our quality criteria were discarded: a full description of the primers, PCR conditions and quality controls has been described previously (Cardenas et al 2013;Clark et al 2012) and is provided in the Supplementary Information. We did not quantify archaeal 16S rRNA genes: previous results indicated that they were 100-times less frequent than bacteria in our soils and the vast majority were ammonia oxidizers, so would be enumerated by the primers for archaeal amoA (Zhalnina et al 2013).…”
Section: Soil Samplingmentioning
confidence: 99%